Deaf Futures: Challenges in Accessing Health Care Services - Swannack, Robyn Danielle (Social Anthropology, 2020)
The purpose of this research is to explore the structural forces that limit the access to health care services for Deaf people. Literature has acknowledged the disconnection between the Deaf and hearing worlds, particularly in health care. Much of the existing literature exploring these fields have failed to include input from the Deaf community members. As such, hearing perspectives dominate the research and hence also in the lives of Deaf individuals. The narrative presented indicates that hearing people need to be made more aware of Deaf people’s own perspectives and respect the policy of self-representation so that laws and regulations do not negatively affects Deaf people’s lives. Using ethnographic methods, including narratives, participant observation, informal and semi-structured interviews, and photo-elicitation interviews, this study highlights the structural violence experienced in accessing health care by six Deaf people in Cape Town, South Africa. The findings confirm previous studies’ assertions that the dominant biomedical view towards deafness negatively affects Deaf people overall, particularly because of lack of communication access to health care.